Re-Creation, Re-Membrance, and Resurgence: Richard Wagamese’s Indian Horse - Celia Cores Antepazo (Canada and Beyond)
This article examines the novel Indian Horse (2012), written by Ojibwe Wabaseemoong Independent Nations member Richard Wagamese (1955-2017) at the height of the Truth and Reconciliation Commission era. Wagamese finds inspiration in the testimonies and experiences of hundreds of victims of Canada’s residential school system, including those of his own family members. The article contextualizes the novel in the Truth and Reconciliation Commission era and explores Saul’s narrative journey to recover his suppressed memories of personal and collective abuse at St. Jerome’s Indian Residential School through the lens of Indigenous resurgence and grounded normativity. Thus, the paper draws on Michi Saagiig scholar Leanne Betasamosake Simpson’s writings on Indigenous radical resurgence to explore the retrieval of Indigenous ways of existing in the world as the way towards decolonization and Indigenous sovereignty. The paper argues that Saul is able to overcome his trauma-induced amnesia, born from the necessity to endure and adapt, and to escape the spiral of shame, isolation, and self-destruction in which he engages only after he embraces discursive Indigenous ways of healing. Wagamese therefore constructs a narrative in which the protagonist’s development mirrors the ideal that the author sets for Canada, in which reconciliation with Indigenous truth will not take place unless the whole story is acknowledged.